Implantable and Injectable Biomaterial Scaffolds for Cancer Immunotherapy - Li, Jie; Luo, Yiqian; Li, Baoqin; Xia, Yuanliang; Wang, Hengyi; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2020)
Cancer immunotherapy has become an emerging strategy recently producing durable immune responses in patients with varieties of malignant tumors. However, the main limitation for the broad application of immunotherapies still to reduce side effects by controlling and regulating the immune system. In order to improve both efficacy and safety, biomaterials have been applied to immunotherapies for the specific modulation of immune cells and the immunosuppressive tumor microenvironment. Recently, researchers have constantly developed biomaterials with new structures, properties and functions. This review provides the most recent advances in the delivery strategies of immunotherapies based on localized biomaterials, focusing on the implantable and injectable biomaterial scaffolds. Finally, the challenges and prospects of applying implantable and injectable biomaterial scaffolds in the development of future cancer immunotherapies are discussed.